Investment Incentives and Market Power: An Experimental Analysis - Dean V. Williamson; Céline Jullien; Lynne Kiesling; Carine Staropoli (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2006)
We examine investment incentives and market power in an experimental market. We characterize market power as the strategic interdependence of subjects' investment decisions and output decisions. The market is designed so that investment and output decisions can be jointly characterized as strategies within a game. A Nash-Cournot equilibrium of the game provides a way of characterizing how investment incentives and market power interact. Subjects could invest in two different production technologies and could produce output to serve as many as two different demand conditions. The technologies were analogous to "baseload" capacity and "peaking" capacity in wholesale electricity markets. The Nash-Cournot benchmark constituted a good indicator of subjects' output decisions in that output cycled around the Cournot benchmark. Thus, on average, consumers extracted the surplus available to them in the equilibrium. While we do not observe Edgeworth Cycles in prices or outputs, we do see them in the producer surplus series. Producers dissipated some of the surplus they could have extracted in the equilibrium by overinvesting in peaking capacity and underinvesting in baseload capacity. Inefficient investment diminished total system efficiency, but producers' investments in total production capacity tracked the Nash-Cournot benchmark. In contrast, monopoly explanations such as collusion do not characterize the data.
Keywords: C92; D43; C72; 330; capacity investment; Cournot; supply function equilibrium; Edgeworth Cycles; market power; electricity markets; investment incentives